2008
DOI: 10.3150/08-bej139
|View full text |Cite
|
Sign up to set email alerts
|

The Dagum family of isotropic correlation functions

Abstract: A function $\rho:[0,\infty)\to(0,1]$ is a completely monotonic function if and only if $\rho(\Vert\mathbf{x}\Vert^2)$ is positive definite on $\mathbb{R}^d$ for all $d$ and thus it represents the correlation function of a weakly stationary and isotropic Gaussian random field. Radial positive definite functions are also of importance as they represent characteristic functions of spherically symmetric probability distributions. In this paper, we analyze the function \[\rho(\beta ,\gamma)(x)=1-\biggl(\frac{x^{\be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…While a range of various stochastic models has been developed [1,2], the approximations do not hold when random fields (RFs) with fractal and, in addition, Hurst characteristics are involved. Indeed, such media are typically encountered in nature [3] and a quite novel mathematical tool to represent and rapidly simulate them has recently been developed in the form of Dagum and Cauchy RFs [4,5]. In fact, the fractal and Hurst characteristics can not only be captured with them, but also decoupled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a range of various stochastic models has been developed [1,2], the approximations do not hold when random fields (RFs) with fractal and, in addition, Hurst characteristics are involved. Indeed, such media are typically encountered in nature [3] and a quite novel mathematical tool to represent and rapidly simulate them has recently been developed in the form of Dagum and Cauchy RFs [4,5]. In fact, the fractal and Hurst characteristics can not only be captured with them, but also decoupled.…”
Section: Introductionmentioning
confidence: 99%
“…Formally, the ensemble average u satisfies 4) where the superscript −1 denotes the inverse, although solving this equation explicitly is generally impossible. One is therefore tempted to replace the above equation by 5) which implies a straightforward averaging of L prior to solving equation (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…(b) The Matérn model is very popular also because it is very handy; having a closed form for the related spectrum, it has been widely used, for instance, to apply Yadrenko's (1983) theory for the equivalence of GRF measures. But there are other covariance functions, such as the generalized Cauchy (Gneiting and Schlather, 2004) and the Dagum (Berg et al, 2008) functions, which allow the separation of the fractal dimension and the Hurst effect of the associated GRF. This is a significant advantage for statistical estimation, and such a property is not offered by the Matérn covariance, which has light tails.…”
mentioning
confidence: 99%
“…This property trivially follows from Theorem 3.2 if 0 < α ≤ 1 and δ > 0. Porcu et al (2007) showed complete monotonicity for other parameter configurations, and their results were extended in Berg et al (2008).…”
Section: Representations Of the Limit Lawsmentioning
confidence: 72%